2004
DOI: 10.1074/jbc.m401276200
|View full text |Cite
|
Sign up to set email alerts
|

The Trypanosoma brucei Cyclin, CYC2, Is Required for Cell Cycle Progression through G1 Phase and for Maintenance of Procyclic Form Cell Morphology

Abstract: CYC2 is an essential PHO80-like cyclin that forms a complex with the cdc2-related kinase CRK3 in Trypanosoma brucei. In both procyclic and bloodstream form T. brucei, knock-down of CYC2 by RNA interference (RNAi) led to an accumulation of cells in G 1 phase. Additionally, in procyclic cells, but not in bloodstream form cells, CYC2 RNAi induced a specific cell elongation at the posterior end. The G 1 block, as well as the posterior end elongation in the procyclic form, was irreversible once established. Stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 39 publications
(43 reference statements)
4
64
1
Order By: Relevance
“…tbTRF RNAi arrested bloodstream and procyclic cells at different stages of the cell cycle, suggesting that the checkpoint mechanisms differ in these two life cycle stages. Consistent with this possibility, different cyclins are used in bloodstream and procyclic stages to control cell-cycle progress (28,69). Interestingly, the overexpression of hTRF1 in procyclic T. brucei also resulted in S-phase arrest, though the phenotypes are not exactly the same as with tbTRF RNAi (52).…”
Section: Discussionmentioning
confidence: 73%
“…tbTRF RNAi arrested bloodstream and procyclic cells at different stages of the cell cycle, suggesting that the checkpoint mechanisms differ in these two life cycle stages. Consistent with this possibility, different cyclins are used in bloodstream and procyclic stages to control cell-cycle progress (28,69). Interestingly, the overexpression of hTRF1 in procyclic T. brucei also resulted in S-phase arrest, though the phenotypes are not exactly the same as with tbTRF RNAi (52).…”
Section: Discussionmentioning
confidence: 73%
“…Previous publications have suggested that nuclear DNA replication or mitosis does not have to be completed in order for cytokinesis to occur (15,28). Silencing of UMSBP results in cell-cycle arrest and impedes mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Seven of the 10 cyclins resemble the budding yeast PHO80 cyclin, which is involved in signaling phosphate starvation, whereas the other three cyclins are homologous to the mitotic B-type cyclins found in animals and plants (41). RNA interference (RNAi)-mediated silencing of some of these cyclins demonstrated that CYC2 plays a major role in promoting G 1 /S transition (43,70) and that CYC4 likely plays a minor role in G 1 /S transition (70). RNAi of CRK1 or CRK2 also arrests the trypanosome cells at the G 1 phase, suggesting their roles in the G 1 /S transition (109,110).…”
Section: Regulation Of the G 1 /S Transitionmentioning
confidence: 99%